Organizational potential as a means of managing the development of rural areas - Abayev, A.A. (BUKETOV BUSINESS REVIEW, 2018)
The article considers the features of organizational management of sustainable functioning of rural territories, which ensure their compliance with market requirements due to organizational capacity. The main attention is paid to the study of the formation of organizational capacity structures: static and dynamic approaches. The author analyzes various interpretations of the concept of "organizational potential". The article notes that the concept of organizational capacity includes a system of values, personnel, structure, information, processes, procedures. The author of the article systemizes the functions of the organizational potential: structuring, integrating, stabilizing, communicative, adaptive and developing. The main factors that determine the use of the potential in the industry in agricultural areas are described. The article considers organizational principles in accordance with the law on state regulation of the development of the agro-industrial complex and rural areas. The author defines a set of resources (financial, land, natural, labor, information), which are the basis for the functioning of the organizational potential of rural areas. The article defines the components of sustainable development potential in rural areas: financial potential, production potential, labor potential and information potential. The role of the State Program for the Development of the Agro-Industrial Complex of the Republic of Kazakhstan for 2017-2021 in the sustainable development of rural areas is defined. The author offers a number of recommendations on the development of the organizational potential of rural areas.